Monitoring Pesticide Residues in Nepal’s Fruits and Vegetables : A Review of Practices, Gaps, and Solutions - Thapa, Sushmita; Pandey, Pradyumna Raj (Nepalese Horticulture, 2025)
Nepal’s fruit and vegetable sector has expanded rapidly in recent decades, but this growth has been accompanied by escalating concerns over the excessive and poorly regulated use of synthetic pesticides. This review provides a critical analysis of current pesticide use trends, residue monitoring efforts, and the persistent gaps in regulatory enforcement, technical infrastructure, and institutional coordination. Despite some progress, existing surveillance systems remain limited in scope, focusing mainly on organophosphates and carbamates, leaving approximately 87% of commonly used pesticides undetected. Drawing insights from comparative experiences in countries such as Thailand, India, and Uganda, the paper underscores the need for a more comprehensive, risk-based monitoring model. Such a system would blend field-ready technologies including acetylcholinesterase biosensors, lateral flow assays, and portable spectroscopy with centralized laboratory confirmation using GC-MS/MS and QuEChERS protocols. A phased implementation approach is proposed, encompassing the expansion of lab facilities, integration of digital data systems, improved traceability mechanisms, and stronger coordination among relevant institutions. Collectively, these strategies are essential not only for protecting public health but also for restoring consumer trust, boosting export potential, and steering Nepal’s horticultural systems toward a safer and more sustainable future.